Film material for laser transfer printing

By using multi-layer structural film materials in laser transfer technology, optimizing material composition and thickness, combining specific additives and support layers, the problem of easy deformation and demolding of a single material is solved, achieving more efficient and accurate Laser transfer process.

CN119217826AActive Publication Date: 2024-12-31WUHAN DR LASER TECH CORP LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411377834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

In the existing laser transfer technology, flexible polymer materials made of a single material are prone to deform in the transfer film, resulting in increased costs and increased energy consumption, and are prone to distortion and demolding difficulties during the graphics processing, which affects the transfer accuracy and quality.

Method used

The film material with a multi-layer structure includes a slurry transfer layer and a laser transmission layer bonded to the adhesive layer. The material composition and thickness of the surface, intermediate and bottom layers are optimized, and the mold release agent, slip agent and opening agent are added. Combining the heat-resistant curing glue layer and the bidirectional stretch polymer as the support layer, the melting point and processing temperature are reduced, and the film's resistance to deformation and mold release properties are improved.

Benefits of technology

It effectively improves the resistance to deformation of the film material during pattern processing and slurry filling, reduces material cost and energy consumption, improves the accuracy and efficiency of laser transfer, and ensures the reliability and stability of the film material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119217826A_ABST
    Figure CN119217826A_ABST
Patent Text Reader

Abstract

The invention discloses a film material for laser transfer printing, and belongs to the technical field of laser transfer printing, the film material comprises a slurry transfer printing layer and a laser transmission layer which are bonded into a whole through an adhesive layer, and the slurry transfer printing layer is of a multi-layer structure comprising a surface layer, a middle layer and a bottom layer. And preferably designing material components, a mixing ratio and a set thickness of each structural layer, and adding corresponding assistants in the surface layer and the middle layer to finally obtain the film material suitable for laser transfer printing. The film material for laser transfer printing is simple in structure and reliable in performance, application in the laser transfer printing operation process can be effectively met, the arrangement and use reliability of the film material in the pattern processing process, the slurry filling process and the slurry laser transfer printing process is guaranteed, the slurry laser transfer printing efficiency and precision are improved, and the film material is suitable for large-scale popularization and application. The service life of the film material used as a transfer printing film is prolonged, and good practical value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser transfer, and in particular relates to a film material used for laser transfer. Background Art

[0002] In the process of photovoltaic cell processing, laser transfer, as a non-contact grid line electrode processing method, can prepare grid line electrodes with a large aspect ratio. It is increasingly used in the field of photovoltaic cell processing. With the development of photovoltaic cell technology and the increase in demand, higher requirements are placed on the efficiency and quality of laser transfer.

[0003] Existing laser transfer requires the preparation of a transparent carrier with a specified transfer pattern (groove), and the use of a scraper to fill the photovoltaic slurry into the groove of the transparent carrier; a specific wavelength laser is used to scan the back of the groove area of ​​the transparent carrier to transfer the slurry in the groove to the silicon wafer under the transparent carrier.

[0004] In the above-mentioned laser transfer process, the transparent carrier is usually set as a film, called a transfer film, and its quality and performance stability will directly affect the quality of laser transfer. At present, single-material flexible polymer materials, such as PP (polypropylene), PE (polyethylene), and APET (amorphous polyethylene terephthalate), are more commonly used for laser transfer. Among them, due to the small tensile strength and elastic modulus of PP or PE, it is difficult to adapt to the tension that the film needs to bear during the transfer film graphic processing and transfer process, and it is very easy to deform; usually, in order to resist deformation, it is necessary to increase the film thickness, which not only increases the material cost, but also has an adverse effect on its subsequent use. At the same time, in the graphic processing of the transfer film, its processing temperature often needs to be close to or higher than the melting point of the material, and PP will increase the processing energy consumption due to its high melting point (160~170℃). In addition, in the process of transfer graphic processing, due to the thermal shrinkage of the polymer material, the graphic will be distorted (the line will bend) after hot pressing, especially the film made of PE, its excessive distortion will affect the alignment of the laser and the graphic during the transfer process.

[0005] Although amorphous PET has certain advantages in mechanical strength, during the transfer process, the film material will come into contact with the transfer slurry. The chemical reagents in the slurry, such as butyl carbitol and terpineol, will cause stress cracking of amorphous PET.

[0006] In addition, the applicant discovered during the research that the prior art has the problem of difficulty or even inability to demold when preparing the transfer pattern; or, due to the excessive demolding force, the processed structure does not meet the requirements, affecting the process effect at the transfer end; or, after the transfer film is completed, it is still faced with friction and extrusion in the process of filling the photovoltaic slurry into the grooves of the transparent carrier with a scraper, resulting in severe scratches on the surface and structural changes, affecting the final use effect. Summary of the invention

[0007] In response to one or more of the above defects or improvement needs of the prior art, the present invention provides a film material for laser transfer, which can effectively ensure the reliability and stability of the transfer film during the graphic processing, slurry filling and laser transfer processes, and reduce the material cost and energy consumption cost of laser transfer.

[0008] To achieve the above object, the present invention provides a film material for laser transfer, which includes a slurry transfer layer and a laser transmission layer bonded together by an adhesive layer; The slurry transfer layer is a multi-layer structure, the melting point of the portion used for processing the transfer pattern is not more than 135°C, and includes a surface layer, an intermediate layer and a bottom layer bonded to the adhesive layer on one side, which are arranged in sequence from the outside to the inside; and the sum of the thickness of the surface layer and the intermediate layer is not less than the groove depth of the transfer pattern; The main components of the surface layer and the middle layer are a mixture of LDPE and HDPE or a mixture of LDPE, HDPE and EVA; and the main component of the bottom layer is LDPE or LLDPE; The surface layer contains 1% to 2% of a release agent, 1% to 2% of a lubricant, and 0 to 1% of an opening agent, which accounts for 1% to 2% of the mass of the main component; the middle layer contains 1% to 2% of a release agent; and no auxiliary agent is added to the bottom layer.

[0009] As a further improvement of the present invention, the adhesive layer is a heat-resistant curing glue layer, and its heat-resistant temperature is not less than 120°C; and / or The adhesive layer is formed by polyurethane adhesive or organic silicone adhesive; and / or The laser transmission layer is a support layer of a film material, which is made of BOPET or BOPA.

[0010] As a further improvement of the present invention, the release agent is a silicone masterbatch; and / or The lubricant is one or more of oleamide, erucamide, stearamide and polyethylene wax.

[0011] As a further improvement of the present invention, the opening agent is one or more of talc, diatomaceous earth, calcium hydrogen phosphate, and SiO2.

[0012] As a further improvement of the present invention, the thickness of the slurry transfer layer is not less than 30 μm; and / or The thickness of the adhesive layer is not greater than 2 μm; and / or The thickness of the laser transmission layer is not less than 25 μm.

[0013] As a further improvement of the present invention, in the slurry transfer layer, the thickness ratio of the surface layer, the middle layer and the bottom layer is (2-3):4:(2-3).

[0014] As a further improvement of the present invention, the groove is prepared by a hot embossing process, and after hot pressing, the lubricant migrates to the groove wall and surface.

[0015] As a further improvement of the present invention, the main components of the surface layer and the middle layer are both a mixture of LDPE and HDPE, wherein the mass fraction of LDPE is 80-90wt%, and the mass fraction of HDPE is 10-20wt%.

[0016] As a further improvement of the present invention, the main components of the surface layer and the middle layer are a mixture of LDPE, HDPE and EVA, wherein the mass fraction of HDPE is 10-20wt%, and the mass fraction of the remaining substances is 80-90wt%; Among the remaining substances, the mass fraction of EVA is 10-60wt%, and the mass fraction of LDPE is 20-80wt%.

[0017] As a further improvement of the present invention, the melt index of LDPE is 2-4 g / 10 min, the melt index of EVA is 3-4 g / 10 min, and the melt index of HDPE is 2-3 g / 10 min.

[0018] The above-mentioned improved technical features can be combined with each other as long as they do not conflict with each other.

[0019] In general, compared with the prior art, the above technical solution conceived by the present invention has the following beneficial effects: (1) The film material for laser transfer in the present invention comprises a slurry transfer layer and a laser transmission layer bonded together by an adhesive layer. The slurry transfer layer is set to a multilayer structure including a surface layer, an intermediate layer and a bottom layer, and the material composition, mixing ratio and thickness of each structural layer are optimally designed. In combination with the addition of corresponding additives in the surface layer and the intermediate layer, a film material suitable for laser transfer is finally obtained. The film material effectively meets the performance requirements when used as a transfer film, facilitates the demolding of the graphic mold during the transfer graphic processing, and ensures the film material's ability to resist deformation during the processing of graphics, slurry filling and slurry transfer, thereby ensuring the accuracy of slurry laser transfer.

[0020] (2) The film material for laser transfer of the present invention optimizes the material and type of the adhesive layer so that its performance can be matched with that of the slurry transfer layer. At the same time, by optimizing the material of the laser transmission layer and coordinating its performance design, it can effectively provide support for the pattern processing of the film material and its use as a transfer film, reduce the deformation of the transfer film material during pattern processing, slurry filling, and slurry transfer, and improve the accuracy of laser transfer.

[0021] (3) The film material for laser transfer of the present invention can further ensure the accuracy of film material preparation by optimizing the types of release agent, lubricant and opening agent, improve the performance of the film material during graphic processing and slurry transfer, reduce the difficulty of film material demolding, improve the quality of graphic processing, and provide conditions for ensuring the accuracy of subsequent slurry transfer.

[0022] (4) The film material for laser transfer of the present invention further specifically defines the proportion of the main components of the surface layer and the middle layer in the slurry transfer layer, so that the performance of the film material after preparation is more controllable, and the adaptability of the film material in the application scenario of the transfer film is further improved, thereby obtaining a film material with a stable structure and excellent performance.

[0023] (5) The film material used for laser transfer in the present invention has a simple structure and reliable performance, and can effectively meet the application requirements of the laser transfer operation process, ensure the reliability of the setting and use of the film material during the graphic processing process, the slurry filling process, and the slurry laser transfer process, improve the efficiency and accuracy of the slurry laser transfer, and have good practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1Schematic diagram of the structure of a film material used for laser transfer in an embodiment of the present invention; Figure 2 is a cross-sectional schematic diagram of a film material for laser transfer in an embodiment of the present invention after pattern processing; In all the drawings, the same reference numerals represent the same technical features, specifically: 1. Slurry transfer layer; 101. Surface layer; 102. Intermediate layer; 103. Bottom layer; 2. Adhesive layer; 3. Laser transmission layer; 4. Groove. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0027] In the description of the present invention, it should be understood that, unless otherwise expressly specified and limited, the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like to indicate orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0028] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0029] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0030] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0031] Example: See also Figure 1 The film material for laser transfer in the preferred embodiment of the present invention is a multi-layer structure, which includes a slurry transfer layer 1 and a laser transmission layer 3 which are bonded together by an adhesive layer 2. Among them, the surface of the slurry transfer layer 1 on the side away from the laser transmission layer 3 is used for processing the transfer pattern, and a groove 4 for filling the transfer slurry can be formed after the pattern processing. The laser transmission layer 3 is located on the side of the film material away from the transfer pattern. As the base part of the film material, it plays the role of maintaining the structural shape of the film material and supporting the film material to complete the laser transfer process.

[0032] Specifically, for the film material in the preferred embodiment, it needs to be laser transferred. To ensure the reliability of laser transfer, it is necessary to ensure that the film material has a high transmittance to a laser of a specific wavelength (processing laser), and the transmittance is preferably not less than 90%.

[0033] At the same time, for the slurry transfer layer 1 in the preferred embodiment, it is necessary to process the transfer pattern, that is, a transfer groove 4 with a certain depth and a specific pattern is processed on the surface of the slurry transfer layer 1 according to the transfer needs, so as to fill the transfer slurry in the transfer groove 4 later. Figure 2 As shown in, it is understandable that Figure 2 In the figure, a rectangular groove is used as an example. In practical application, the groove may be an inverted trapezoidal groove or a triangular groove, etc. It can be understood by those skilled in the art that when the groove is an inverted trapezoidal or triangular groove, the groove width refers to the width at the opening.

[0034] It is understood that the film material used for laser transfer in the preferred embodiment of the present invention, as an application of laser transfer, requires not only good laser transmittance, but also the following properties: On the one hand, it needs to have good processing performance so that the groove 4 of the transfer pattern can be hot-pressed and formed; on the other hand, it needs to have sufficient flexibility and strength so that the photovoltaic slurry can be scraped into the groove 4 with a scraper without causing excessive deformation or damage to the film material. In addition, it also needs to have good slurry corrosion resistance and polarity so that the transfer layer (including the groove) is not damaged by the slurry, and the photovoltaic slurry can be well filled in the groove 4, so that a transfer grid line electrode closer to the groove design size can be obtained.

[0035] After research, the applicant sets the slurry transfer layer 1 as a multi-layer structure, which at least includes a surface layer 101, an intermediate layer 102 and a bottom layer 103 arranged in sequence from the outside to the inside along the thickness direction; wherein the surface layer 101 is located on the side of the slurry transfer layer 1 away from the adhesive layer 2, and the bottom layer 103 is arranged on the side close to the adhesive layer 2, which is used to fix and adhere to the laser transmission layer 3 through the adhesive layer 2 to form a membrane material with an integrated structure.

[0036] In actual settings, the main component of the slurry transfer layer 1 in the preferred embodiment is polyolefin, and its processing temperature is low when processing the groove 4 pattern, and it has good resistance to chemical reagents, which can ensure the stability and reliability of the film material performance during the reaction with the slurry.

[0037] More specifically, for the slurry transfer layer 1 in the preferred embodiment, the main components of the surface layer 101 and the middle layer 102 are preferably the same, and are further preferably a mixture of LDPE (low-density polyethylene) and HDPE (high-density polyethylene), or a mixture of LDPE, HDPE and EVA (ethylene-vinyl acetate copolymer). At the same time, in the preferred embodiment, the main component of the bottom layer 103 in the slurry transfer layer 1 is LDPE or LLDPE (linear low-density polyethylene).

[0038] Among them, in the mixture of LDPE and HDPE, the mass fraction of LDPE is 80~90wt%, any range value or point value therebetween, and the mass fraction of HDPE is 10~20wt%, any range value or point value therebetween.

[0039] In the mixture of LDPE, HDPE and EVA, the mass fraction of HDPE is 10~20wt%, any range value or point value in between, and the mass fraction of the remaining substances is 80~90wt%, any range value or point value in between. For example, the mass fraction of EVA is 10~60wt%, any range value or point value in between, and the mass fraction of LDPE is 20~80wt%, any range value or point value in between.

[0040] In more detail, the melt index of LDPE is 2 to 4 g / 10 min, with any range or point value therebetween, the melt index of EVA is 3 to 4 g / 10 min, with any range or point value therebetween, and the melt index of HDPE is 2 to 3 g / 10 min, with any range or point value therebetween.

[0041] Since the processing temperature of EVA and LDPE can be controlled within 115°C, and EVA can even be controlled within 105°C. Therefore, based on the material selection of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1, the difficulty of the film material for (groove 4) pattern processing can be effectively reduced, and the energy consumption can be reduced, which can effectively reduce the cost of transfer processing. In a preferred embodiment, the melting point of the part used for processing the transfer pattern is preferably not more than 135°C, and more preferably not more than 125°C.

[0042] At the same time, since the hardness of HDPE is higher than that of LDPE (LDPE Shore hardness is 40~50D, LDPE Shore hardness is 65~70D), after adding HDPE to LDPE, the hardness of the film material is higher than that of LDPE alone, which is between LDPE and HDPE.

[0043] However, the melting temperature of LDPE is below 115°C, or even below 110°C; while the melting temperature of HDPE is generally above 130°C. After HDPE is mixed into LDPE to form a blend, there are two situations for its melting temperature: (1) The two are completely compatible, and the differential thermal analysis curve of the blend shows only one melting peak, and the melting point peak is between LDPE and HDPE; (2) The two are partially compatible, and the differential thermal analysis curve of the blend shows two melting peaks, one appears at a position where the melting peak of LDPE is offset to a higher temperature, and the other appears at a position where the melting peak of HDPE is offset to a lower temperature.

[0044] That is, the addition of HDPE will result in a higher melting point of the blend than LDPE, and when the amount of HDPE added is controlled at a low level, such as within 20%, the blend is often partially compatible. At this time, the original LDPE graphic processing temperature only needs to be increased by 5~10°C to perform graphic processing. Since the blend is not completely melted when the temperature is increased by 5~10°C, the surface adhesion between the mold and the film material will be reduced (compared to the single LDPE graphic processing), thereby reducing the demoulding force, avoiding the problem of poor laser transfer accuracy caused by the large demoulding force affecting the processing accuracy of the groove 4.

[0045] In another preferred embodiment, the slurry transfer layer 1 is a blend of LDPE, HDPE and EVA. Since EVA has a low melting point, usually below 100°C, the graphic processing temperature of its blend with LDPE and HDPE is lower than that of the aforementioned LDPE and HDPE blend, and the addition of EVA can improve the surface polarity of the film material, allowing the photovoltaic slurry to better contact and fill the groove 4.

[0046] Furthermore, in addition to the aforementioned main components, a certain mass percentage of auxiliary agents is added to the slurry transfer layer 1. In a preferred embodiment, a release agent accounting for 1% to 2% of the mass of the main components, any range value or point value in between, a slip agent of 1% to 2%, any range value or point value in between, and an opening agent of 0% to 1%, any range value or point value in between are added to the surface layer 101; a release agent of 1% to 2%, any range value or point value in between are added to the middle layer 102; and correspondingly, no auxiliary agents are added to the bottom layer 103.

[0047] In more detail, the lubricant in the preferred embodiment is one or more of oleamide, erucamide, stearic acid amide, polyethylene wax, and fluoropolymer; the release agent is silicone masterbatch; and the opening agent is preferably one or more of talc, diatomaceous earth, calcium hydrogen phosphate, and SiO2.

[0048] Since the film material needs to process the groove 4 in the surface layer 101 when performing graphic processing, after adding the release agent in the surface layer 101, it can be used to improve the processing performance of the plastic particles when processing into the film, and lubricate the film surface and the mold surface, thereby reducing the demolding force, ensuring a good demolding effect when processing the groove 4 and ensuring the processing accuracy of the groove 4, thereby ensuring the processing accuracy during laser transfer.

[0049] At the same time, the lubricant has a similar effect to the release agent on one hand, which lubricates the film surface and the mold surface to reduce the demoulding force; on the other hand, the lubricant also reduces the friction coefficient of the film surface, which facilitates the film to travel during the processing. In addition, since the lubricant reduces the friction coefficient of the film surface, it is also helpful to reduce the scratches on the film surface caused by the scraper when the scraper scrapes the slurry into the groove 4, avoiding the slurry filling problem caused by the damage to the edge of the groove 4, thereby improving the transfer quality and extending the service life of the film material.

[0050] However, the reason why the lubricant is added only to the surface layer 101 is to reduce its migration to the adhesive layer 2 during the film processing, so as to prevent the lubricant from migrating to the adhesive layer 2 and affecting the bonding strength between the bottom layer 103 and the laser transmission layer 3 .

[0051] In addition, the opening agent is mainly used to prevent adhesion between films and avoid affecting the processing of the film material itself and the winding and unwinding during the groove 4 processing.

[0052] More specifically, the actual thickness of the slurry transfer layer 1 is preferably not less than 30 μm, and the thickness ratio of the surface layer 101, the middle layer 102, and the bottom layer 103 is preferably (2-3):4:(2-3), for example 3:4:3 or 1:2:1.

[0053] Through the composition and proportion of the main components of the surface layer 101, the middle layer 102 and the bottom layer 103 in the above technical solution, as well as the setting of the auxiliary agent, the surface layer 101 has good processability, is easy to demould, and is easy to prepare the groove 4 pattern. It has a certain strength, so that the scraper can easily scrape the slurry into it to form a good filling, and has good polarity and slurry corrosion resistance, so that the photovoltaic slurry can be well filled in the groove 4, and can be better separated from the groove 4 to achieve transfer when the laser is irradiated. At the same time, the main component of the middle layer 102 is the same as that of the surface layer 101, and the auxiliary agent is slightly different, which can prevent the slip agent from migrating to the adhesive layer 2 and affecting the peel strength of the film material, thereby ensuring that the bottom layer 103 can have a good bonding effect with the slurry transfer layer 1 through the adhesive layer 2. In addition, the bottom layer 103 is a single resin component with good laser transmittance, and can achieve good bonding with the laser transmission layer 3 through the adhesive layer 2.

[0054] In more detail, in a preferred embodiment, the slurry transfer layer 1 needs to be provided with a groove 4 of a transfer pattern, and the groove 4 is prepared by hot pressing, and the pressing temperature is further preferably 115° C. After hot pressing, the lubricant migrates to the groove wall and the surface layer to form an enrichment, which can reduce the friction coefficient of the film surface and reduce the damage of the scraper to the film. At the same time, the slurry can also be filled more densely in the groove.

[0055] In specific settings, the thickness of the slurry transfer layer 1 is preferably 30-45 μm, and the thickness ratio of the surface layer 101, the middle layer 102 and the bottom layer 103 is preferably 3:4:3 or 1:2:1. At the same time, in actual settings, the depth of the groove 4 will not reach the bottom layer 103, that is, the depth of the groove 4 does not exceed the middle layer 102, that is, the sum of the thickness of the surface layer 101 and the middle layer 102 is not less than the depth of the groove 4 of the transfer pattern, for example Figure 2 as shown in .

[0056] In a specific preferred embodiment, the bottom of the groove 4 is at least 2µm away from the bottom layer 103, that is, the sum of the thickness of the surface layer 101 and the middle layer 102 is at least 2µm greater than the depth of the groove 4. At the same time, the spacing between two adjacent grooves 4 is preferably 0.1mm-1.2mm.

[0057] Furthermore, the thickness of the adhesive layer 2 is preferably not greater than 2 μm, and it is further preferably a heat-resistant curing glue layer with a heat-resistant temperature of not less than 120° C., ensuring that the adhesive layer 2 does not flow, decompose or deform significantly when the slurry transfer layer 1 is subjected to graphic processing.

[0058] In actual preparation, the adhesive layer 2 selected in the preferred embodiment can be preferably made of any one of polyurethane adhesive and organic silicone adhesive.

[0059] In addition, when actually preparing the laser transmission layer 3, in addition to ensuring its light transmittance, it is also necessary to ensure that its mechanical properties and heat resistance are good. In a preferred embodiment, the laser transmission layer 3, as a supporting layer of the film material, is responsible for maintaining structural stability during the pattern processing and subsequent transfer operation of the slurry transfer layer 1, reducing structural deformation during the film material processing and working process, and ensuring the processing accuracy of the groove 4, thereby ensuring the accuracy of laser transfer.

[0060] In a preferred embodiment, the material of the laser transmission layer 3 can be BOPET (biaxially oriented polyethylene terephthalate film) or BOPA (biaxially oriented nylon film). Taking BOPET as an example, it has good mechanical properties (stiffness, tensile strength, tensile modulus, etc.), and a thinner thickness can provide a good tensile resistance effect; at the same time, since BOPET has a low thermal shrinkage rate, it can resist the structural bending caused by the shrinkage of the slurry transfer layer 1 during graphic processing, so that the graphic structure bending is controlled within a smaller range.

[0061] For example, for a single LDPE film, its structural curvature after pattern processing can reach 50~100μm; while for a multi-layer composite film of LDPE and BOPET, its structural curvature after pattern processing can be controlled within 5~20μm, which is conducive to the precise alignment of the laser and the filling slurry during the transfer operation.

[0062] More preferably, during actual preparation, the thickness of the laser transmissive layer 3 is preferably not less than 25 μm, and further preferably 36 μm or 50 μm.

[0063] Meanwhile, in the preferred embodiment, the tensile strength of the laser transmission layer 3 is not less than 150 MPa, the heat-resistant temperature is not less than 180° C., and the thermal shrinkage rate at 150° C. for 30 minutes is not greater than 1%.

[0064] Through the above-mentioned settings, a film material with good structural stability and structural performance that meets the requirements of laser transfer film can be obtained, which fully guarantees the convenience of demolding the film material during graphic processing, and ensures the film material's anti-deformation ability during graphic processing, slurry filling and transfer, reduces the power consumption of the film material, and improves the accuracy of slurry laser transfer.

[0065] As follows, the aforementioned membrane material is further described through several specific preferred embodiments.

[0066] Embodiment 1: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE and HDPE.

[0067] The melt index of LDPE in the surface layer 101 is 2 g / 10 min, and the mass ratio is 90 wt %; the mass ratio of HDPE is 10 wt %, and the melt index of HDPE is 2 g / 10 min.

[0068] At the same time, silicone masterbatch accounting for 2 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 1 wt % of the main component is added as a lubricant.

[0069] Secondly, compared with the surface layer 101, the main component setting in the middle layer 102 is the same as that of the surface layer 101, and the added proportion and material type of the release agent are also the same. The only difference is that the lubricant is not added.

[0070] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no additives are added to the bottom layer 103 .

[0071] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0072] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 0.8, and the spacing between adjacent grooves is 1.2 mm.

[0073] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0074] Embodiment 2: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE and HDPE.

[0075] The melt index of LDPE in the surface layer 101 is 2 g / 10 min, and the mass ratio is 80 wt %; the mass ratio of HDPE is 20 wt %, and the melt index of HDPE is 2 g / 10 min.

[0076] At the same time, silicone masterbatch accounting for 1 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 1 wt % of the main component is added as a lubricant.

[0077] Secondly, compared with the surface layer 101, the main component setting in the middle layer 102 is the same as that of the surface layer 101, and the added proportion and material type of the release agent are also the same. The only difference is that the lubricant is not added.

[0078] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no additives are added to the bottom layer 103 .

[0079] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0080] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 0.8, and the spacing between adjacent grooves is 1.2 mm.

[0081] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0082] Embodiment 3: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE and HDPE.

[0083] The melt index of LDPE in the surface layer 101 is 2 g / 10 min, and the mass ratio is 85 wt %; the mass ratio of HDPE is 15 wt %, and the melt index of HDPE is 2 g / 10 min.

[0084] At the same time, silicone masterbatch accounting for 1.5 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 1 wt % of the main component is added as a lubricant.

[0085] Secondly, compared with the surface layer 101, the main component setting in the middle layer 102 is the same as that of the surface layer 101, and the added proportion and material type of the release agent are also the same. The only difference is that the lubricant is not added.

[0086] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no additives are added to the bottom layer 103 .

[0087] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0088] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 0.8, and the spacing between adjacent grooves is 1.2 mm.

[0089] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0090] Embodiment 4: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE and HDPE.

[0091] The melt index of LDPE in the surface layer 101 is 4 g / 10 min, and the mass ratio is 80 wt %; the mass ratio of HDPE is 20 wt %, and the melt index of HDPE is 3 g / 10 min.

[0092] At the same time, silicone masterbatch accounting for 2 wt% of the main component is added to the surface layer 101 as a release agent, erucic acid amide accounting for 2 wt% of the main component is used as a lubricant, and SiO2 accounting for 1 wt% of the main component is used as an opening agent.

[0093] Secondly, compared with the surface layer 101, the main component setting in the middle layer 102 is the same as that of the surface layer 101, and the added proportion and material type of the release agent are also the same. The only difference is that the lubricant and the opening agent are not added.

[0094] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no additives are added to the bottom layer 103 .

[0095] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0096] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 0.8, and the spacing between adjacent grooves is 1.2 mm.

[0097] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0098] Embodiment 5: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE, HDPE and EVA.

[0099] Among them, the melt index of EVA is 3g / 10min, and the VA (vinyl acetate) content in EVA is not more than 12%. Correspondingly, the melt index of LDPE is 2g / 10min, and the melt index of HDPE is 2g / 10min.

[0100] In more detail, the mass ratio of HDPE in the surface layer 101 is 10 wt %, the mass ratio of LDPE is 80 wt %, and the mass ratio of EVA is 10 wt %.

[0101] At the same time, silicone masterbatch accounting for 2 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 1 wt % of the main component is added as a lubricant.

[0102] Compared with the surface layer 101 , no lubricant is added to the middle layer 102 of this embodiment, and the arrangement of other components is the same as that of the surface layer 101 .

[0103] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no other additives are added to the bottom layer 103 .

[0104] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0105] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 1, and the spacing between adjacent grooves is 1.2 mm.

[0106] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0107] Embodiment 6: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE, HDPE and EVA.

[0108] Among them, the melt index of EVA is 3g / 10min, and the VA (vinyl acetate) content in EVA is not more than 12%. Correspondingly, the melt index of LDPE is 2g / 10min, and the melt index of HDPE is 2g / 10min.

[0109] In more detail, the mass ratio of HDPE in the surface layer 101 is 20wt%, the mass ratio of LDPE is 40wt%, and the mass ratio of EVA is 40wt%.

[0110] At the same time, silicone masterbatch accounting for 2 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 2 wt % of the main component is added as a lubricant.

[0111] Compared with the surface layer 101 , no lubricant is added to the middle layer 102 of this embodiment, and the arrangement of other components is the same as that of the surface layer 101 .

[0112] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no other additives are added to the bottom layer 103 .

[0113] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0114] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 1, and the spacing between adjacent grooves is 1.2 mm.

[0115] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0116] Embodiment 7: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE, HDPE and EVA.

[0117] Among them, the melt index of EVA is 3g / 10min, and the VA (vinyl acetate) content in EVA is not more than 12%. Correspondingly, the melt index of LDPE is 2g / 10min, and the melt index of HDPE is 2g / 10min.

[0118] In more detail, the mass ratio of HDPE in the surface layer 101 is 20wt%, the mass ratio of LDPE is 20wt%, and the mass ratio of EVA is 60wt%.

[0119] At the same time, silicone masterbatch accounting for 2 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 2 wt % of the main component is added as a lubricant.

[0120] Compared with the surface layer 101 , no lubricant is added to the middle layer 102 of this embodiment, and the arrangement of other components is the same as that of the surface layer 101 .

[0121] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no other additives are added to the bottom layer 103 .

[0122] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0123] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 1, and the spacing between adjacent grooves is 1.2 mm.

[0124] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0125] Embodiment 8: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE, HDPE and EVA.

[0126] Among them, the melt index of EVA is 3g / 10min, and the VA (vinyl acetate) content in EVA is not more than 12%. Correspondingly, the melt index of LDPE is 4g / 10min, and the melt index of HDPE is 3g / 10min.

[0127] In more detail, the mass ratio of HDPE in the surface layer 101 is 10 wt %, the mass ratio of LDPE is 80 wt %, and the mass ratio of EVA is 10 wt %.

[0128] At the same time, silicone masterbatch accounting for 1 wt% of the main component is added to the surface layer 101 as a release agent, erucic acid amide accounting for 2 wt% of the main component is added as a lubricant, and SiO2 accounting for 1 wt% of the main component is added as an opening agent.

[0129] Compared with the surface layer 101 , no lubricant or anti-blocking agent is added to the middle layer 102 of this embodiment, and the arrangement of other components is the same as that of the surface layer 101 .

[0130] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no other additives are added to the bottom layer 103 .

[0131] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0132] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 1, and the spacing between adjacent grooves is 1.2 mm.

[0133] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0134] Embodiment 9: In this embodiment, the main components of the surface layer 101 and the middle layer 102 of the slurry transfer layer 1 are both a blend of LDPE, HDPE and EVA.

[0135] Among them, the melt index of EVA is 4g / 10min, and the VA (vinyl acetate) content in EVA is not more than 12%. Correspondingly, the melt index of LDPE is 2g / 10min, and the melt index of HDPE is 2g / 10min.

[0136] In more detail, the mass ratio of HDPE in the surface layer 101 is 10 wt %, the mass ratio of LDPE is 80 wt %, and the mass ratio of EVA is 10 wt %.

[0137] At the same time, silicone masterbatch accounting for 2 wt % of the main component is added to the surface layer 101 as a release agent, and erucic acid amide accounting for 2 wt % of the main component is added as a lubricant.

[0138] Compared with the surface layer 101 , no lubricant is added to the middle layer 102 of this embodiment, and the arrangement of other components is the same as that of the surface layer 101 .

[0139] Furthermore, the bottom layer 103 of the slurry transfer layer 1 is made of LLDPE, the melt index of which is 2 g / 10 min, and no other additives are added to the bottom layer 103 .

[0140] In more detail, in this embodiment, the thicknesses of the surface layer 101, the middle layer 102, and the bottom layer 103 are 12 μm, 16 μm, and 12 μm, respectively.

[0141] Meanwhile, when pattern processing is performed on the film material in this embodiment, the groove depth is 20 μm, the aspect ratio of the groove is 1, and the spacing between adjacent grooves is 1.2 mm.

[0142] In addition, the adhesive layer 2 of the film material is a two-component polyurethane glue with a thickness of less than 2 μm. Correspondingly, the laser transmission layer 3 is made of a BOPET material with a thickness of 50 μm.

[0143] Comparative Example 1: In this embodiment, the setting form of the adhesive layer 2 and the laser transmission layer 3 is consistent with that in Example 1, except that the slurry transfer layer has only one layer of LDPE with a melting index of 2g / 10min, and the thickness is the same as the overall thickness of the slurry transfer layer 1 in Example 1.

[0144] Comparative Example 2: In this embodiment, the arrangement of the adhesive layer 2 and the laser transmission layer 3 is consistent with that in Embodiment 1, the only difference being that no auxiliary agent is added to the surface layer, the middle layer and the bottom layer of the slurry transfer layer 1 .

[0145] Comparative Example 3: In this embodiment, the arrangement of the adhesive layer 2 and the laser transmission layer 3 is consistent with that in Embodiment 1, and the only difference is that 1 wt % of erucamide is added as a lubricant in the middle layer of the slurry transfer layer 1 .

[0146] Comparative Example 4: In this embodiment, the arrangement of the adhesive layer 2 and the laser transmission layer 3 is consistent with that in Embodiment 7, with the only difference being that 2 wt % of erucamide is added as a lubricant in the middle layer of the slurry transfer layer 1 .

[0147] By performing pattern processing and laser transfer operations on the slurry transfer layer 1 on the film materials obtained in the above-mentioned Examples 1 to 9 and Comparative Examples 1 to 4, the comparison results shown in the following Table 1 were obtained.

[0148] Table 1 Comparison of the effects of membrane materials in Examples 1 to 9 and Comparative Examples 1 to 4

[0149] According to Table 1, it can be seen that according to the film materials prepared in the above-mentioned Examples 1 to 9, due to the selection of polyolefin materials in the component materials and the design of the component ratio, the graphic processing temperature can be reliably controlled below 125°C, and the graphic processing difficulty and processing energy consumption are both low. In addition, due to the layered configuration of auxiliary agents such as release agents and lubricants, the demoulding force is controlled in a relatively low range during graphic processing, and the microstructure does not undergo obvious shape and size changes due to the pulling of the demoulding force after molding, and the film does not undergo stratification. In addition, due to the selection of heat-resistant and low-shrinkage BOPET, the overall structural deformation after graphic processing is controlled in a relatively low range (all less than 25μm), indicating that the overall performance of graphic processing is good.

[0150] In contrast, for comparative examples 1 to 4 that do not adopt the technical solutions designed in the aforementioned preferred embodiments, the prepared film materials are difficult to use as transfer films for laser transfer, and have defects such as difficulty in demolding and / or film material stratification during graphic processing, and cannot meet the actual transfer process requirements.

[0151] In addition, through more detailed comparison, it can be found that in Examples 1 to 4, due to the addition of an appropriate proportion of HDPE, the surface hardness of the film is improved, and the surface scratches caused by the scraper when filling the slurry at the transfer end will be reduced; in Examples 5 to 9, HDPE has the same effect, and at the same time, due to the addition of an appropriate proportion of EVA, the filling density of the slurry in the pattern is better when the transfer end is used, and the height of the transferred grid line electrode can be made slightly higher; however, when the amount of EVA added is large, the overall hardness of the film surface will decrease, and the pattern will deform downward more after the scraper is pressed down, and the slurry is filled at this time. After that, the scraper scrapes over and the deformation recovers, resulting in a larger unfilled space on the shallow surface after the pattern is filled, and the actual width after the slurry is filled will decrease (the microstructure is generally set to an inverted trapezoid), thereby obtaining a narrower grid line electrode.

[0152] The film material used for laser transfer in the present invention has a simple structure and reliable performance, can effectively meet the application requirements of laser transfer operations, ensure the reliability of the setting and use of the film material during graphic processing, slurry filling and slurry laser transfer, improve the efficiency and accuracy of slurry laser transfer, extend the life of the film material when used as a transfer film, and has good practical value.

[0153] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A film material for laser transfer, characterized in that: It includes a slurry transfer layer and a laser transmission layer bonded together by an adhesive layer; The slurry transfer layer is a multi-layer structure, the melting point of the portion used for processing the transfer pattern is not more than 135°C, and includes a surface layer, an intermediate layer and a bottom layer bonded to the adhesive layer on one side, which are arranged in sequence from the outside to the inside; and the sum of the thickness of the surface layer and the intermediate layer is not less than the groove depth of the transfer pattern; The main components of the surface layer and the middle layer are a mixture of LDPE and HDPE or a mixture of LDPE, HDPE and EVA; and the main component of the bottom layer is LDPE or LLDPE; The surface layer contains 1% to 2% of a release agent, 1% to 2% of a lubricant, and 0 to 1% of an opening agent, which accounts for 1% to 2% of the mass of the main component; the middle layer contains 1% to 2% of a release agent; and no auxiliary agent is added to the bottom layer.

2. The film material for laser transfer according to claim 1, characterized in that: The adhesive layer is a heat-resistant curing glue layer, and its heat-resistant temperature is not less than 120°C; and / or The adhesive layer is formed by polyurethane adhesive or organic silicone adhesive; and / or The laser transmission layer is a support layer of a film material, which is made of BOPET or BOPA.

3. The film material for laser transfer according to claim 1 or 2, characterized in that: The release agent is silicone masterbatch; and / or The lubricant is one or more of oleamide, erucamide, stearamide and polyethylene wax.

4. The film material for laser transfer according to claim 3, characterized in that: The opening agent is one or more of talc, diatomaceous earth, calcium hydrogen phosphate, and SiO2.

5. The film material for laser transfer according to claim 1, 2 or 4, characterized in that: The thickness of the slurry transfer layer is not less than 30 μm; and / or The thickness of the adhesive layer is not greater than 2 μm; and / or The thickness of the laser transmission layer is not less than 25 μm.

6. The film material for laser transfer according to claim 1, 2 or 4, characterized in that: In the slurry transfer layer, the thickness ratio of the surface layer, the middle layer and the bottom layer is (2-3):4:(2-3).

7. The film material for laser transfer according to claim 6, characterized in that: The groove is prepared by a hot embossing process, and after hot pressing, the lubricant migrates to the groove wall and surface.

8. The film material for laser transfer according to claim 1, 2, 4 or 7, characterized in that: The main components of the surface layer and the middle layer are both a mixture of LDPE and HDPE, wherein the mass fraction of LDPE is 80-90wt%, and the mass fraction of HDPE is 10-20wt%.

9. The film material for laser transfer according to claim 1, 2, 4 or 7, characterized in that: The main components of the surface layer and the middle layer are a mixture of LDPE, HDPE and EVA, wherein the mass fraction of HDPE is 10-20wt%, and the mass fraction of the remaining substances is 80-90wt%; Among the remaining substances, the mass fraction of EVA is 10-60wt%, and the mass fraction of LDPE is 20-80wt%.

10. The film material for laser transfer according to claim 1, 2, 4 or 7, characterized in that: The melt index of LDPE is 2~4g / 10min, the melt index of EVA is 3~4g / 10min, and the melt index of HDPE is 2~3g / 10min.

Citation Information

Patent Citations

  • Method and device of transferring an impression from a substrate to a surface

    CN106163787A

  • Transfer sheet

    CN119301209A

  • Transfer printing substrate

    CN217214737U

  • Laser transfer film and photovoltaic cell

    CN217993923U

  • Pattern transfer method and apparatus, flexible display panel, flexible solar cell, electronic book, thin film transistor, electromagnetic-shielding sheet, and flexible printed circuit board applying thereof

    US20110209749A1